Concurrent validity of Myotest for assessing explosive strength indicators in countermovement jump - Vladimír Hojka; James J. Tufano; Tomáš Malý; Petr Šťastný; Radim Jebavý; Jan Feher; František Zahálka; Tomáš Gryc (Palacký University Olomouc, 2018)
Background: Previous research has determined the validity and reliability of accelerometer-based devices, but the findings are not consistent. Objective: The purpose of this study was to determine the validity of an accelerometer (Myotest PRO) for measuring explosive strength indicators (jump height, peak force, peak velocity, and peak power) during the countermovement jump. Methods: Thirty-three university students (22 males and 11 females; 178.6 ± 5.6 cm, 69.3 ± 6.5 kg, 21.8 ± 1.7 years) performed five individual countermovement jumps. Jump height was derived from an accelerometer (Myotest, frequency 200 Hz), optic timing system (Optojump) and from a force plate (Kistler, frequency 800 Hz) using both flight time and force impulse algorithms. Peak force, peak velocity, and peak power were calculated by the accelerometer and force plate. Results: The Myotest resulted in systematic bias, overestimating jump height by 8.0 ± 2.1 cm (p < .001) compared to force impulse algorithm; flight time algorithm by 5.5 ± 2.0 cm (p < .001) using the force plate and by 5.9 ± 2.0 cm (p < .001) using the Optojump. The Myotest also underestimated peak force by 167 ± 182 N (p < .001). Compared to force impulse algorithm, the Myotest displayed less agreement for peak velocity (r2 = .245) and peak power (r2 = .557). Conclusion: Accelerometers are valid and may be used consistently to evaluate countermovement jump height. However, they are not valid, and should neither be used to measure peak force, velocity, or power nor be compared against other methods due to a bias.